Edukasi Pencegahan dan Penanggulangan Bullying Pada Santri di TPQ AL-Hakim Blimbing Kota Malang - Sulistyorini, Anita; An-Khofiyya, Nida; Fitri, Rihadatus Syahwana; Chalisah, Siti Nur; Abdilla, Mohammad Nurul Faiz; Adhitama, Felicia Dewati Elit; Syechfiansyah, Rossie (Prosiding Seminar Kesehatan Nasional Sexophone, 2024)
Some students at TPQ Al-Hakim have been victims of bullying. Bullying carried out by students is physical and verbal bullying, physical bullying carried out such as hitting, pushing, choking and kicking. While verbal bullying, such as mocking by calling other students by their parents' names, calling them bad names, cursing, and insulting. In addition, the TPQ Al-Hakim teacher said that the bullying that occurred made some students not want to participate in activities or leave TPQ after experiencing bullying from their friends. Objectives: This service is to increase knowledge and foster awareness in students and teachers about the negative impact of bullying, this education is prioritized for students to create a safe and free environment from bullying behavior. Methods: Service activities in the form of counseling related to bullying are carried out directly by visiting children who are studying at TPQ Al-Hakim, Blimbing District, Malang City. Method is carried out in order to interact directly through counseling methods as an effort to prevent and overcome bullying in children in the TPQ Al-Hakim environment, Blimbing District, Malang City. Results This activity can be considered a success because the participants were very responsive and active during the question and answer session, material presentation, and also the post-test with true-false games. 85% of students experienced an increase in knowledge about bullying after the true-false game.